Особливості виробничої прози в українській радянській літературі: повість Дмитра Бузька «Домни» - Ткаченко, М. (Слово і Час, 2021)
У статті висвітлено специфіку виробничої прози в українській радянській літературі 30-х років. З’ясовано основні формальні та змістові ознаки виробничих жанрів, простежено їх рецепцію в критиці.
На основі аналізу повісті Дмитра Бузька «Домни» розкрито стильові, жанрові, сюжетні, образні й тематичні принципи моделювання виробничих романів та повістей. The paper highlights the features of industrial prose in the Ukrainian Soviet literature of
the 1930s clarifying the main formal and semantic characteristics of industrial genres, their
reception in criticism, and such characteristics of this genre as style, plot, figurative and thematic
principles. Based on D. Buzko’s text “Blast Furnaces”, the paper shows the transitional
period between the free avant-garde artistic movement in Ukraine of the 1920s and the
implementation of socialist realism as the only official style in Soviet art in the 1930s. As a
representative of the futurist movement, deeply engaged in the elaboration of early cinema
theories, Dmytro Byzko wrote a novel “Holiandiia”, which deconstructed official narratives
and topics of the late 1920s. The comparison of the “Blast furnaces” with this novel helps
not only to see the mentioned transition but also to notice the divergence of the “Blast furnaces”
and more canonical pieces of this genre. Dmytro Buzko’s “Blast furnaces” extremely
accurately reflects the expectations from literature at that time: the heroes explain the main
stages of work at the metallurgical plant, and by their example, in words and deeds, agitate
readers to become conscious builders of socialism. Although a large number of similar techniques,
ideas, and even views of the author can be found in “Holiandiia” and “Blast furnaces”,
the first novel is a sharp critique of the contemporary reality, while “Blast furnaces” is a text
complementary to reality. The analysis of “Blast furnaces” shows the process of the search
for an ideal and canonical protagonist as well as an antagonist for the Soviet literature. The
last one in this text is represented by the typical for the whole Ukrainian literature covetous
farmer who, in a new political reality, plays a role of a small evil ready to harm ordinary
workers and socialistic future.